Key stakeholders and platforms/networks in food systems transformation in Viet Nam in 2022-2024 - Huynh Thi, Tuyen Thanh; Pham Thi, Huong Mai; Duong, Thanh Thi; Nguyen, Quoc Minh; Herens, Marion (2024)
The stakeholder identification process was initiated under the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) initiative to determine with whom the project needs to engage to achieve food systems transformation. It consolidates all stakeholders working on food system issues into a ‘living’ database that enables the rapid identification of potential stakeholders in each of the SHIFT focal countries. Understanding, engaging, and capacitating diverse food system stakeholders will bring varied perspectives to foster collaborations and drive transformative actions across the system, ultimately improving outcomes. This stakeholder identification is a foundational step toward understanding who (individuals and institutions) is involved in food system issues at various governance levels, including public and private actors, as well as those operating in formal and informal sectors at national, regional, and local government level. In addition, the SHiFT country engagement approach aims to connect with and strengthen existing stakeholder coordination mechanisms or platforms in the domain of food systems transformation, rather than establish new collaborative structures. By applying a stakeholder platform mapping tool to identify coordination structures engaged in food system issues, existing platforms and networks can be effectively recognized.